The Effect of Leverage, Sales Growth, Cash Flow on Financial Distress with Corporate Governance as a Moderating Variable - Giarto, Rizka Vidya Dwi; Fachrurrozie, Fachrurrozie (Universitas Negeri Semarang, 2020)
The aim of this study is to detect the effect of leverage, sales growth, and cash flow on financial distress with corporate governance as moderating variable. This research used all of basic and chemical sector manufacturing companies listed on the Indonesian Stock Exchange (IDX 2013-2017 period, there were 69 companies. Sampling used with purposive sampling technique and selected 31 companies with 152 analysis units. The data was analysed by descriptive statistical analysis and logistic regression for inferential statistical. The Results show that leverage has significant positive effect to financial distress. Sales growth has no significant effect to financial distress. Cash flow has a significant negative effect to financial distress. Corporate governance measured by managerial ownership is be able to weaken the positive effect of leverage and strengthen the negative effect of sales growth to financial distress, but not be able to strengthen the negative effect of cash flow to financial distress. The conclusions in this research are just leverage and cash flow have significantly effect to financial distress, as well as corporate governance only able to moderate the effect of leverage and sales growth to financial distress.